The Influence of Transformational Leadership, Talent Management, and Work Discipline on Organisational Effectiveness Through Competence - Pia Agustina; Desy Prastyani (International Publisher (YAPENBI), 2025)
Organizational Effectiveness reflects the ability of an organization to achieve its goals, manage resources efficiently, and adapt to environmental changes. An effective organization is not only characterized by the achievement of business targets but also by its internal ability to optimally manage human resources, workflows, and organizational culture. This research aims to analyze the influence of Transformational Leadership, discipline, and Talent Management on Organizational Effectiveness among employees of the Ministry of Cooperatives and SMEs. This type of research is quantitative with purposive sampling techniques distributed through a questionnaire to 250 respondents who are employees of the Ministry of Cooperatives and SMEs located in the Jakarta area. Primary data analysis is conducted using Structural Equation Modeling (SEM) methods. The research results show that Transformational Leadership, discipline, and Talent Management have a positive and significant effect on Organizational Effectiveness. These three independent variables were chosen because they are considered to play a strategic role in enhancing Organizational Effectiveness in the face of increasingly complex and competitive work environment dynamics. Thus, each hypothesis tested in this study has proven to have a significant impact. These findings provide important implications for organizational management in efforts to create a productive and results-oriented work environment.